Pengaruh ROA (Return On Asset) dan ROE (Return On Equity) terhadap Harga Saham pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Hoerunnisa, Najwa Aulia; Sulistiyo, Hari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
In this study, researchers aim to determine Return on Asset and Return on Equity affect or do not affect the share price of banking sector companies listed on the Indonesia Stock Exchange Partially or Simultaneously. The use of samples in this study are companies in the bangking sector listed on the Indonesian Stcok Exchange for the 2018 – 2020 period. With the sampling technique in the study using purposive sampling technique. The data used by the research is a secondary data collection method. The data analysis technique in the study was statistical analysis, classical assumption test and hypothesis testing. It can be concluded from the test results that Partially ROA has a significant effect on Stcock Prices and ROE has no significant effect on Stock Prices. Keywords: ROA, ROE, Stock Prices.